PENGARUH MOTIVASI TERHADAP GAIRAH KARJA GURU PADA SMP NEGERI 2 BELITANG OKUTIMUR - Setia Kurniawan (STIE Trisna Negara OKU Timur, 2020)
Teachers are learning agents who have a very important role in educating the nation to achieve educational goals. As a learning agent, teachers must have a passion for work in carrying out their duties. If they do not have a passion for work, how can they guide their students to achieve the specified minimum learning competencies? Therefore, work passion is a problem that needs to be given a solution through motivation. This study aims to determine whether motivation has an effect on work passion, with the object of research being the teachers at SMP Negeri 2 Belitang OKU Timur. The hypothesis proposed is that